Tecendo uma história : a Cooperativa Têxtil Galópolis - Ferri, Marlos Rodrigo (My University, 2019)
The present research deals with the creation of a textile cooperative that was born from a workers' strike in 1999, in the municipality of Caxias do Sul, in a working-class neighborhood where a recognized wool mill is located. From its bankruptcy, these workers who have an old history founded a cooperative, similar to that which gave rise 100 years before the old woolen mill. This story recounts the history of Italian emigrants who were expelled from a large woolen industry in Italy in the late nineteenth century. The research had as object the analysis of the construction of this cooperative that through Oral History gave voice to the multiple narratives of workers involved in this process. The study theoretically discusses the role of cooperativism and shows ways of organizing cooperatives, identifying how this organization was structured by the workers since the 1999 strike and how they dealt with the bankruptcy of the Sehbe wool mill. The research discusses the financial difficulties that the wool goes through, which began with the opening of the national market after the implantation of neoliberal policies in the country in the early 1990s. It also discusses the ways in which the administration of the company was conducted in that period which resulted in a general strike in late 1990. The union's help, after months of back pay, a large part of the employees and many negotiations, made it possible to create the cooperative as a solution to the difficulties encountered. For many, it was not just the livelihood that was at stake, but a life of dedication and hard work. The creation of the textile cooperative of Galopolis is a demonstration of the union of workers who managed with the help of the union to pay a labor debt and at the same time to take over the factory park, giving a new life to the collective work. The research describes through the narratives of these workers how this process of resistance of the workers occurred. The research contributes to the teaching of local history, and has been created as an illustrative material of this history.
A presente pesquisa trata da criação de uma cooperativa têxtil que nasce de uma greve operária em 1999, no município de Caxias do Sul, num bairro operário onde se localiza um reconhecido lanifício. A partir de sua falência, esses operários que possuem uma história antiga fundam uma cooperativa, semelhante a que deu origem cem anos antes ao antigo lanifício. Essa história remete a história de emigrantes italianos que foram expulsos de uma grande indústria de lã na Itália no final do século XIX. A pesquisa teve como objeto a análise da construção dessa cooperativa que por meio da História Oral deu voz às múltiplas narrativas de operários envolvidos nesse processo. O estudo discute teoricamente o papel do cooperativismo e mostra formas de organizar cooperativas, identificando como foi estruturada essa organização pelos operários a partir da greve de 1999 e de como lidaram com a falência do lanifício Sehbe. A pesquisa discorre sobre as dificuldades financeiras que o lanifício passa, as quais, começaram com a abertura do mercado nacional após a implantação das políticas neoliberais no país, no início dos anos 1990. Discorre também sobre as formas de como foi conduzida a administração da empresa nesse período que resulta no final de 1990, em uma greve geral. A ajuda do sindicato, após meses de salários atrasados, de grande parte dos funcionários e muitas negociações, possibilitou a criação da cooperativa, como solução às dificuldades encontradas. Para muitos, não era apenas a forma de sustento que estava em jogo, mas uma vida de dedicação e de muito trabalho. A criação da cooperativa têxtil de Galópolis é uma demonstração da união de operários que conseguiram com a ajuda do sindicato pagar uma dívida trabalhista e ao mesmo tempo arrematar o parque fabril, dando uma nova vida ao trabalho coletivo. A pesquisa descreve por meio das narrativas desses operários como se deu esse processo de resistência dos trabalhadores. A pesquisa contribui para o ensino de história local, tendo sido criado como produto um material ilustrativo dessa história.
Keywords: Cooperativa Têxtil Galópolis; Indústria têxtil - Galópolis (Caxias do Sul, RS) - História; Textile industry - Galópolis (Caxias do Sul, Brazil) - History